PENGARUH PLAYFULNESS, GOOD PRICE FOR MONEY & IMBALAN TERHADAP NIAT PEMBELIAN DIDALAM APLIKASI DENGAN MOBILE GAME LOYALTY SEBAGAI PEMEDIASI PADA PENGGUNA APLIKASI GAME MOBILE LEGENDS DI BANDA ACEH - Muhammad Zasqi Anbiya; Syarifah Evi Zuhra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to measure the role of Playfulness, Good Price for Money, Rewards and Mobile Game Loyalty towards Intention to Purchase in Applications for mobile Legends online mobile game application users in Banda Aceh. The sample used in this study is the user of the online mobile game application Mobile Legends in Banda Aceh, amounting to 200 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is convenience sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved.Based on the HLM results, it indicates that Playfulness has a positive effect on Intention Purchases in the Application, Good Price for Money has a positive effect on Intention Purchases in the Application, Rewards has a positive effect on Intention Purchases in the Application, Playfulness has a positive effect on Mobile Game Loyalty, Good Price for Money has a negative effect to Mobile Game Loyalty, Rewards have a positive effect on Mobile Game Loyalty, Mobile Game Loyalty has a positive effect on Intention to Purchase in the Application, Mobile Game Loyalty partially mediates the Playfulness relationship to Purchase Intention in the Application, Mobile Game Loyalty fully mediates the Good Price for Money relationship Intention to Purchase in the Application and Mobile Game Loyalty partially mediates the relationship of Rewards to the Intention to Purchase in the Application.Penelitian ini bertujuan untuk mengukur peranan Playfulness, Good Price for Money, Imbalan dan Mobile Game Loyalty terhadap Niat Pembelian didalam Aplikasi pada pengguna aplikasi game mobile online Mobile Legends di Banda Aceh. Sampel yang digunakan dalam penelitian ini adalah pengguna aplikasi game mobile online Mobile Legends di Banda Aceh yang berjumlah 200 responden. Peralatan pengumpulan data yang digunakan pada penelitian ini adalah kuesioner. Teknik pengambilan sampel yang digunakan adalah convenience sampling. Hierarchical Linear Modelling (HLM) digunakan sebagai metode analisis untuk mengetahui pengaruh dari semua variabel-variabel yang terlibat.  Berdasarkan hasil HLM, mengindikasikan bahwa Playfulness berpengaruh positif terhadap Niat Pembelian didalam Aplikasi, Good Price for Money berpengaruh positif terhadap Niat Pembelian didalam Aplikasi, Imbalan berpengaruh positif terhadap Niat Pembelian didalam Aplikasi, Playfulness berpengaruh positif terhadap Mobile Game Loyalty, Good Price for Money berpengaruh negatif terhadap Mobile Game Loyalty, Imbalan berpengaruh positif terhadap Mobile Game Loyalty, Mobile Game Loyalty berpengaruh positif terhadap Niat Pembelian didalam Aplikasi, Mobile Game Loyalty memediasi secara parsial hubungan Playfulness terhadap Niat Pembelian didalam Aplikasi, Mobile Game Loyalty memediasi secara penuh hubungan Good Price for Money terhadap Niat Pembelian didalam Aplikasi dan Mobile Game Loyalty memediasi secara parsial hubungan Imbalan terhadap Niat Pembelian didalam Aplikasi.